Comparative Assessment of Stress Indicators and Cognitive Impairment Rates of Teachers - AZEEZ, Eniola Morufat (Ilorin Journal of Education, 2023)
Teachers are of paramount importance in the society as they spearhead the transmission of the society’s knowledge, values and skills to the next generation. However, like every other professional in a cognitively demanding job, they are often likely to experience stress and could sometimes be subjected to cognitive impairments and neurodegenerative diseases. This study investigated the relationship between stress levels experience by teachers and their level of cognition. One hundred and fifty teachers were randomly selected for this study. Two research instruments were administered, the perceived stress scale and the self-administered gerocognitve examination to measure the stress experienced by teachers and to measure cognition respectively. Results showed that the majority of the teachers were generally subjected to moderate levels of stress and the level of stress experienced by teachers is not influenced by their gender or their age group. Correlative analysis between the perceived stress scale and the self-administered gerocognitive tests showed that there is a negligible relationship between the stress score of the teacher and their cognition levels. Efforts should be made to reduce the stress teachers are exposed to in order to protect them from cognitive impairment.